Burden of disease among older adults in Europe—trends in mortality and disability, 1990–2019. (24th November 2022) - Iburg, Kim Moesgaard; Charalampous, Periklis; Allebeck, Peter; Stenberg, Elsa Jonsson; O'Caoimh, Rónán; Monasta, Lorenzo; Peñalvo, José L; Pereira, David M; Wyper, Grant M A; Niranjan, Vikram; Devleesschauwer, Brecht; Haagsma, Juanita
Abstract: Background: It is important to understand the effects of population ageing on disease burden and explore conditions that drive poor health in later life to prevent or manage these. We examined the development of disease burden and its components for major disease groups among older adults in Europe over the last 30 years. Methods: Using data from the Global Burden of Disease 2019 Study, we analyzed burden of disease trends between 1990 and 2019 measured by years of life lost (YLL), years lived with disability (YLD) and disability-adjusted life years (DALYs) among older adults (65+ years) in Western, Central and Eastern Europe using cause groups for diseases and injuries. Results: Between 1990 and 2019, the crude numbers of DALYs for all causes increased substantially among older Western Europeans. In Eastern Europe, the absolute DALYs also increased from 1990 to 2005 but then decreased between 2006 and 2013. However, DALY rates declined for all European regions over time, with large differences in the magnitude by region and gender. Changes in the YLL rate were mainly driven by the contribution of cardiovascular diseases. Conclusions: This study found an increased overall absolute disease burden among older Europeans between 1990 and 2019. The demographic change that has taken place in Eastern European countries implies a potential problem of directed resource allocation to the health care sector. Furthermore, the findings highlight the potential health gains through directing resources to health promotion and treatment to reduce YLDs and to prevent YLLs, primarily from cardiovascular diseases.